Atoxigenic isolates of Aspergillus flavus effectively reduce cyclopiazonic acid in a sorghum-based matrix under simulated abiotic stress conditions - Sharma, V.; Cervini, C.; Verheecke-Vaessen, C.; Bandyopadhyay, R.; Medina, A.; Ortega-Beltran, A.; Magan, N. (Oxford University Press, 2025)
Maize, groundnut, and sorghum are important staple crops in several countries, but are prone to mycotoxin contamination. In the tropics and subtropics, Aspergillus flavus frequently contaminates those crops with aflatoxins and, sometimes, with cyclopiazonic acid (CPA). However, some genotypes cannot produce one or both toxins. In various countries, atoxigenic isolates of A. flavus are formulated into biocontrol products for field use to outcompete aflatoxin producers. The products effectively limit aflatoxin but their utility to reduce CPA remains unexplored. The abilities of four atoxigenic isolates (AF−) from Burkina Faso to control CPA by an isolate with high capacity to produce aflatoxins (AF+) and CPA was tested in co-inoculations at varying ratios (100+, 75+/25−, 50+/50−, 25+/75−, 100−), under simulated abiotic stress conditions. Experiments were conducted on 2% sorghum-based media at 0.95 and 0.90 water activity (aw), at 30°C and 37°C, for 12 days. CPA was quantified using liquid chromatography tandem mass spectroscopy. CPA concentrations gradually decreased as the proportion of atoxigenic isolates increased, with effectiveness varying depending on the environmental conditions.